(untitled) (Agro Productividad, 2024)
Objective: To evaluate the potential methane gas production from corn silages (CS) intended for Holstein cattle in dairy farms in the state of Aguascalientes (Ags), Mexico. Design/Methodology/Approach: Methane (CH4) is one of the greenhouse gases, and worldwide plans and actions are being developed to monitor, control, and reduce their environmental impact. In Mexico, methane emissions from livestock are equivalent to 10.1% of CO2 equivalent are recorded. CS samples were collected from six municipalities in Ags, representing a total of 18 dairy farms. The in vitro gas production technique was used to determine methane gas production, employing a nested mixed model to compare variables between municipalities using residual maximum likelihood method. Results: The average methane production in CS was 29.3 mL/gDM. The Ags municipality showed significantly higher methane production (35.9 mL/gDM, p<0.05), while San Francisco de los Romo (SFR) displayed the lowest production (21.5 mL/gDM, p<0.05). In the state of Aguascalientes, CS-derived CH4 production was projected at approximately 2,884 metric tons (MT) annually. Study Limitations/Implications: There were no identified limitations in the study. Findings/Conclusions: The potential CH4 gas production derived from CS projected in the study represented 0.103% of what was reported by INEGyCEI in 2019.